Worker Commitment and Labour Management Relations under Lean Production at CAMI - Rinehart, James; Huxley, Christopher; Robertson, David (Relations industrielles / Industrial Relations, 1994)
Efforts by CAMI, a unionized Suzuki-General Motors auto plant in Ontario, to construct a workplace characterized by worker commitment and cooperative labour-management relations are examined. Why did these efforts fall? Why, of all the Japanese or joint-venture transplants in North America, was it at CAMI that industrial conflict occurred? Does the experience hold important implications for worker and union responses to lean production in other settings? The findings presented are the result of a longitudinal investigation conducted over a two year period by the CAW Research Group on CAMI. The researchers had an unusual degree of access to the shopfloor, and base many oftheir observations on data drawn from a randomly selected sample of workers.